Evidence of genetic determination of annual movement strategies in medium-sized raptors - Literák, Ivan; Kyseláková, Claudia Maria; Dostál, Marek; Karlsson, Caka; Škrábal, Jan; Skyrpan, Mykola; Hrtan, Ervín; Haraszthy, Lászlo; Raab, Rainer (Scientific reports, 2025)
Most species of migrating birds use a combination of innate vector-based orientation programs and social information to facilitate accurate navigation during their life. A number of various interspecies hybridisations have been reported in birds. The traits of parents are expressed in hybrids in typical ways which are either intermediate, combined or heterotic. Here, we analyse the different migration behaviours of medium-sized raptors, i.e., Red Kites Milvus milvus, Black Kites Milvus migrans, and their hybrids. We chose six well-established parameters to compare the behaviour of Kite hybrids with those of both parental species. When comparing 16 quantified behavioural characteristics between Red Kites and F1 hybrids and between Black Kites and F1 hybrids, significant differences were found in 10 characteristics between Red Kites and F1 hybrids but only one of the 16 characteristics between Black Kites and F1 hybrids. Hence, F1 hybrid individuals showed behaviour much more similar to Black Kites than Red Kites. It implies that the basis of the migratory behaviour of Kites is an innate program with the dominance of genetic determinants supplemented by the use of social learning from individuals of the parent species.
Keywords: Red Kite; Black Kite; Behavior, Animal; Falconiformes; Animals; Hybridisation; chování zvířat; Migration; Animal Migration; Raptors; Hybridization, Genetic; Milvus migrans; zvířata; dravci; Milvus milvus; hybridizace genetická; migrace zvířat